Viral characterization of the reassortants between canine influenza H3N2 and human pandemic (2009) H1N1 and avian H9N2 viruses in canine ex vivo tracheal explants - Tonia T. Kam; Christine H. T. Bui; Hin-Wo Yeung; Peter C. H. Wong; Alex W. H. Chin; John M. Nicholls; Malik Peiris; Kenrie P. Y. Hui; Leo L. M. Poon; Michael C. W. Chan (Virology Journal)
Abstract Background In 2007, the canine influenza H3N2 virus (H3N2-CIV) first emerged in the canine population in South Korea. The virus had since spread internationally and continues to circulate in the canines. While there is currently no report of H3N2-CIV spilling over to the human population, the virus had shown a tendency to reassort with other influenza subtypes. Given that the canine respiratory tract is susceptible to a wide range of influenza viruses, it is of interest whether H3N2-CIV are likely to reassort with human and avian IAVs to generate reassortants with increased zoonotic potential. Methods We conducted a co-infection study in canine tracheal explants. Ex vivo canine tracheal tissues were co-infected by H3N2-CIV and two respective human and avian influenza viruses, 2009 pandemic H1N1 and avian H9N2 virus. The viruses were serially passaged in canine tracheal explants. Next-generation sequencing was conducted to investigate the reassortment pattern. The resulting reassortants were plaque-purified and inoculated in human alveolar epithelial cells to determine their replication competence and proinflammatory cytokine induction profile. Results Co-passaging H3N2-CIV with human/avian influenza A viruses in canine tracheal explants resulted in a high rate of reassortment. Plaque-purified reassortants were all viable and able to propagate in mammalian alveolar epithelial cells. Reassortment most frequently occurred in the MP, NA and NS segments. Selected reassortants had enhanced replication efficiency and able to induce more proinflammatory cytokines than the parental strains, suggesting that these reassortants have a considerable zoonotic risk. Conclusions Our results demonstrate that ex vivo canine tracheal explants can serve as an effective platform for studying influenza virus reassortment and evolution. The ability of H3N2-CIV reassortants to replicate and induce a proinflammatory cytokine response in human alveolar epithelial cells substantiates the zoonotic potential of canine-origin influenza A viruses and suggests a risk of enhanced transmission acquired through reassortment events. These findings highlight the need for ongoing surveillance and constant vigilance regarding influenza viruses circulating in the canine population.